Blade runner 2049 - Villeneuve, Denis, 1967-; Fancher, Hampton; Green, Michael (Michael J.); Kosove, Andrew A.; Gosling, Ryan, 1980-; Ford, Harrison, 1942-; Armas, Ana de, 1988-; Hoeks, Sylvia, 1983-; Wright, Robin, 1966-; Davis, Mackenzie; Juri, Carla, 1985-; James, Lennie; et al. (Burbank, CA : Warner Bros. Home Entertainment, 2018)
A young blade runner's discovery of a long buried secret leads him to track down former blade runner Rick Deckard, who's been missing for thirty years.
Originally released as a motion picture in 2017.
Based on characters from the novel "Do Androids Dream of Electric Sheep" by Philip K. Dick.
Special features: Familiarize yourself with the world of Blade Runner: The replicant evolution; Blade runners; The rise of Wallace Corp; Welcome to 2049; Jois; Within the skies: Spinners, pilotfish and barracudas; Your entry into the visionary spectacle: Designing the world of Blade Runner 2049; To be human: Casting Blade Runner 2049; Prologues: 2022: Black out; 2036: Nexus Dawn; 2048: Nowhere to run.
Originally packaged as a Blu-ray + DVD combo pack.
Director of photography, Roger A. Deakins ; editor, Joe Walker ; music, Benjamin Wallfisch, Hans Zimmer.
Ryan Gosling, Harrison Ford, Ana De Armas, Sylvia Hoeks, Robin Wright, Mackenzie Davis, Carla Juri, Lennie James, Sean Young, Edward James Olmos, Dave Bautista, Jared Leto.
Keywords: Los Angeles (Calif.). -- Police Department -- Drama; Androids -- Drama; Missing persons -- Drama; Thrillers (Motion pictures); Film adaptations; Detective and mystery films; Feature films; Fiction films; Science fiction films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities